The control of disinfection byproducts and their precursors in biologically active filtration processes. (1st November 2017) - Liu, Chao; Olivares, Christopher I.; Pinto, Ameet J.; Lauderdale, Chance V.; Brown, Jess; Selbes, Meric; Karanfil, Tanju
Abstract: While disinfection provides hygienically safe drinking water, the disinfectants react with inorganic or organic precursors, leading to the formation of harmful disinfection byproducts (DBPs). Biological filtration is a process in which an otherwise conventional granular filter is designed to remove not only fine particulates but also dissolved organic matters (e.g., DBP precursors) through microbially mediated degradation. Recently, applications of biofiltration in drinking water treatment have increased significantly. This review summarizes the effectiveness of biofiltration in removing DBPs and their precursors and identifies potential factors in biofilters that may control the removal or contribute to formation of DBP and their precursors during drinking water treatment. Biofiltration can remove a fraction of the precursors of halogenated DBPs (trihalomethanes, haloacetic acids, haloketones, haloaldehydes, haloacetonitriles, haloacetamides, and halonitromethanes), while also demonstrating capability in removing bromate and halogenated DBPs, except for trihalomethanes. However, the effectiveness of biofiltration mediated removal of nitrosamine and its precursors appears to be variable. An increase in nitrosamine precursors after biofiltration was ascribed to the biomass sloughing off from media or direct nitrosamine formation in the biofilter under certain denitrifying conditions. Operating parameters, such as pre-ozonation, media type, empty bed contact time, backwashing, temperature, and nutrient addition may be optimized to control the regulated DBPs in the biofilter effluent while minimizing the formation of unregulated emerging DBPs. While summarizing the state of knowledge of biofiltration mediated control of DBPs, this review also identifies several knowledge gaps to highlight future research topics of interest. Graphical abstract: Highlights: Over 100 papers related to biolfiltration and DBPs were reviewed. Biofiltration was found to remove a fraction of halogenated DBP precursors. Biofiltration was found to decrease concentrations of formed DBPs, except for THMs. Varying degrees of nitrosamine control by biofiltration has been reported. Operating parameters affect the biofiltration performance.